Reduction of Setup Times in a Metal Fabrication Company Using a Lean-Sigma Approach - Celis Gracia, Omar; García-Alcaraz, Jorge Luis; Estrada Orantes, Francisco Javier; Avelar, Liliana; Alba-Baena, Noé (2024)
Manufacturing companies face demand fluctuations and must deliver the required quantity of parts to their customers within the required time; however, companies face different challenges in fulfilling them. One is technological advances, which make it impossible for them to compete with other countries, such as China, due to financial issues. Therefore, manufacturing companies use continuous improvement methodologies to achieve better performance in their processes. Six Sigma and Lean Manufacturing are some of the best-known approaches. This article briefly presents the application of a lean sigma approach oriented to solving problems. This research proposes a methodology based on Lean Sigma that contrasts what different authors currently do: continuous improvement projects that take up to 12 months to produce results and do not solve a problem. This implementation is conducted in a process that manufactures metal parts and fails to deliver them on time to its customers. Using tools such as the Single Minute Exchange of Die (SMED) in a production line, on-time deliveries were increased from 89 % to 96 %; at the same time, the model change times were reduced by approximately 60 %, which is required for the implementation of this methodology for only four weeks, unlike the traditional six-sigma approach that can take up to 12 months to improve the process.